Role of Contrast-Enhanced Ultrasound (CEUS) in the Diagnosis of Cervical Lymph Node Metastasis in Nasopharyngeal Carcinoma (NPC) Patients - Ling, Wenwu; Nie, Ji; Zhang, Dingyue; Yang, Qianru; Jin, Hongyu; Ou, Xuejin; Ma, Xuelei; Luo, Yan (Frontiers in Oncology, 2020)
Objective: The aim of the study was to evaluate the diagnostic value of contrast-enhanced ultrasonography (CEUS) in distinguishing benign from malignant cervical lymph nodes in patients with nasopharyngeal carcinoma (NPC). Material and methods: Totally, 144 NPC patients with enlarged superficial cervical lymph nodes received CEUS examination. CEUS image characteristics of malignant cervical lymph nodes were compared with benign ones. And parameters of the time-intensity curve (TIC) were analyzed, including time to peak (TP), area under the gamma curve (AUC), and peak intensity (PI). Meanwhile, receiver operating characteristic (ROC) curve analysis was carried out to evaluate the diagnostic value of CEUS. Result: Of the 144 lymph nodes examined, 64 were benign nodules and 80 were metastatic nodules. The vast majority of the benign nodes displayed centrifugal perfusion and homogenous enhancement, while most of the malignant nodes showed centripetal perfusion and inhomogeneous. Meanwhile, quantitative analysis showed that CEUS parameters including PI, TP and AUC were significantly higher in benign lymph nodes. The combination of the above three parameters and CEUS image characteristics could get a fine diagnostic value. Conclusion: Our results suggested that imaging Perfusion patterns as well as quantitative parameters obtained from CEUS provided valuable information for the evaluation of cervical lymph nodes in NPC patients.